PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KUALITAS PELAYANAN PADA BADAN PENDAPATAN DAERAH PROVINSI LAMPUNG - M Fikri Akbar; Dewi Dewi (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) Does motivation affect service quality in the Revenue Agency of Lampung Province, (2) Does the work environment affect the service quality of the Lampung Province Regional Revenue Agency, (3) Does motivation and work environment and motivation motivate on Service Quality at the Lampung Province Regional Revenue Agency.The research method used in this study is quantitative. The study population was 93 employees at the Lampung Province Regional Revenue Agency. While the sample is 93 people or a total sample. The research variables are Motivation (X1), and work environment (X2) as independent variables and Service Quality is the dependent variable (Y). To test the hypothesis proposed, analysis techniques are used through Multiple Regression to determine the effect of the independent variable (X1), namely Motivation and (X2) work environment and the dependent variable (Y), namely the quality of service at the Lampung Province Regional Revenue Agency.The results showed that from the adjusted R2 coefficient value of 0.674 which showed that 67.4% of the variation in service quality (YŶ) was determined jointly by motivation (X1) and work environment (X2). The remaining 33.6% is influenced by other causes not included in this research model and still requires further research. R value of 0.821 indicates a strong positive correlation between motivation (X1) and work environment (X2) with service quality (Y). Positive correlation means that ups and downs of service quality always go in the direction of the level of motivation and work environment. If motivation and work environment are at the maximum level, the quality of service will be good too. Conversely, if the motivation and work environment is not good then the quality of service will be bad too. Furthermore, strong correlation means that the results of the above regression tests are very suitable for predicting the simultaneous effect of motivation and work environment on service quality at the Lampung Province Regional Revenue Agency.